Analisis Peran Ilmu Perundang-Undangan Dalam Meningkatkan Kualitas Pembentukan Peraturan Perundang-Undangan Di Indonesia - Asianna Manik; Nabila Amanda Pulungan; Alya Rachma; Erbina Br Sembiring; Risky Sakti Lumban Gaol; Ramsul Nababan; Maulana Ibrahim (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to find out how legislative science contributes to the formation of legislative regulations in Indonesia, what factors influence the quality of legislative regulations in Indonesia, and how the application of legislative science can improve the quality of existing legislative regulations. . Forming laws is an integral part of the task of managing a society consisting of a group of human individuals who have various aspects of life. Therefore, designing and drafting laws that can be accepted by society is a complicated task. The method the author used in this research is a qualitative method using library research, namely conducting research by collecting information from books and journals.